Model Program Pemberdayaan Masyarakat Desa Berbasis Komunitas - Yusuf Adam Hilman; Elok Putri Nimasari (ARISTO, 2018)
This study examines the issue of community empowerment, which is considered to be a solution problem of poverty, which is more interesting when the community of "Janda" becomes an important object. This research focuses on the study of community-based community empowerment model in Janda village. Purpose is able to measure the effectiveness and also the ideal form of community empowerment program model in the village of Janda, Dadapan Village, Balong District, Ponorogo Regency. The research are method qualitative descriptive approach, with object in research is the people members, especially mothers who berrstatus "widow" in the Dadapan Village, Balong District, Ponorogo Regency.. Activities include 1). Training of processed food from the existing agricultural potential, 2). Make a kitchen granary from the land around the community. 3). Train the art activities of mothers who are "Janda". From concluded this research is community empowerment activities in Dadapan Village, Balong District, Ponorogo Regency, which have been done are very focused on "Janda", so that the activity is expected to contribute, to the life of those who is distressed or increase the independence of the family, with this activity, economical but psychologically they will be motivated to become a powerful individual.